PSYCHOLOGICAL USE OF COLORS IN THE FIELD OF MEDICINE: चिकित्सा के क्षेत्र में रंगों का मनोवैज्ञानिक प्रयोग - Kumar Tomar, Ashish (International Journal of Research -GRANTHAALAYAH, 2014)
Color is an integral part of our life. Colors have such a deep relationship with human life that one cannot realize human happiness in a colorless world. It is only through colors that we can see from the greenery of the nature to the golden light of the sun, the blue of the sky, the black of the clouds and the light of the moon. The seven-color rainbow line drawn in the clouds tells a beautiful story of each color. Seeing which the mind becomes a part of the colorful world. Colors also have a definite role in the multi-colored life of human beings. Colors have a profound effect on the human brain. Modern psychologists believe that the likes of color and influence affect the entire equation of a man’s life. This strength of colors has also made it useful for healing. There are many diseases, colors are used for the treatment of them. Due to these characteristics, it has been named color therapy. रंग हमारे जीवन का एक अभिन्न हिस्सा है। रंगों का मानव जीवन के साथ इतना गहरा रिश्ता है कि बेरंग दुनिया में मानव खुशियों का एहसास ही नहीं कर सकता। रंगों के माध्यम से ही प्रकृति की हरियाली से लेकर सूरज की सुनहरी रोशनी, आसमान का नीलापन, बादलों की काली घटाएं और चन्द्रमा का उजलापन देख पाते है। बादलों में खिंचती सात रंगों की इन्द्रधनुषी रेखा प्रत्येक रंग की सुन्दर कहानी बयां करती है। जिसे देखकर मन रंगीन दुनिया का हिस्सा बन जाता है। मनुष्य के बहुरंगों जीवन में रंगों की भी एक निश्चित भूमिका होंती है। रंग मनुष्य के मस्तिष्क पर गहरा असर डालते है। आधुनिक मनोवैज्ञानिकों की मान्यता है कि रंगों की पसन्द व प्रभाव से आदमी की जिन्दगी का पूरा समीकरण प्रभावित होता है। रंगों की इस ताकत ने उसे उपचार के लिए भी उपयोगी बना दिया है। कईं सारी बीमारियाँ है, जिनके उपचार के लिए रंगों का इस्तेमाल किया जाता है। इन खूबियों के कारण इसे कलर थेरेपी यानी रंग चिकित्सा का नाम दिया गया है।